2007
DOI: 10.1590/s1806-37132007000100013
|View full text |Cite
|
Sign up to set email alerts
|

O efeito da adenotonsilectomia na saturação de oxigênio em crianças com distúrbios respiratórios do sono

Abstract: Adenotonsillectomy significantly improved oxygen saturation, as measured through nocturnal pulse oximetry, in children with sleep disordered breathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…We reviewed the current published literature to determine the reliability of using preoperative tonsil and adenoid size as an indicator of adenotonsillectomy success. The results suggest that preoperative tonsil size is not associated with outcome because most studies 6,7,[9][10][11][12][13][14][15][16][17][18][19][20]22 found no direct association between subjective tonsil size and adenotonsillectomy success. The success rate for adenotonsillectomy appeared to be high regardless of tonsil size.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We reviewed the current published literature to determine the reliability of using preoperative tonsil and adenoid size as an indicator of adenotonsillectomy success. The results suggest that preoperative tonsil size is not associated with outcome because most studies 6,7,[9][10][11][12][13][14][15][16][17][18][19][20]22 found no direct association between subjective tonsil size and adenotonsillectomy success. The success rate for adenotonsillectomy appeared to be high regardless of tonsil size.…”
Section: Discussionmentioning
confidence: 82%
“…Tonsil size assessment also varied among studies. Although most studies 5,8,[13][14][15][16][17][18][19]22,24,[26][27][28][29][30][31] applied the Brodsky grading scale, which assigns a grade of 0 to 4 or greater to tonsils based on the severity of hypertrophy, other studies 10,11,21,23 used the Friedman grading scale 34 or a fiber optic grading scale. Only a few studies 8,12,19 additionally graded adenoids on a 1-to 4-point or greater scale.…”
Section: Limitationsmentioning
confidence: 99%
“…A significant and well established association exists between OSDB and several nocturnal HR parameters (Baumert et al, 2016; Evans et al, 2014; Muzumdar et al, 2011). Nocturnal oxygen saturation and HR are important predictors of OSDB severity and have been used to measure responsiveness to OSDB treatment in children (Álvarez et al, 2017; Arrarte et al, 2007; Garde et al, 2013; Mbam et al, 2014). Nevertheless, the diurnal cardiovascular impact in children suffering from OSDB is a less visited topic in the literature (Brockmann, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Adenotonsillectomy may be necessary for patients with respiratory disorders caused by hypertrophy of the tonsils and adenoids; these patients show significant improvements in their oxygen saturation and quality of life after surgery. 7 8 In view of this evidence, we aimed to evaluate the relationship between tonsillar hypertrophy, adenoids, microorganisms, and immunoglobulins in patients with surgical indications.…”
Section: Introductionmentioning
confidence: 99%